PENETAPAN PARAMETER MUTU KRITIS UNTUK MENENTUKAN UMUR SIMPAN KUBIS BUNGA FRESH-CUT - D., Musaddad (CEFARS : JURNAL AGRIBISNIS DAN PENGEMBANGAN WILAYAH, 2011)
Basically the critical limits of shelf-life of food products, including the fresh-cut Cauliflowers, is safe limit of lowest quality can still be accepted by consumers. The objective of this study was to determine the critical quality parameters that can be used in determining the shelf-life limit of fresh-cut cauliflowers. The study was conducted in Postharvest Laboratory, Indonesian Vegetables Research Institute (IVEGRI) on Februari 2012. Determination of critical limits was carried out through five steps activities as follows: 1) preparing the sample; 2) test of quality parameters in an objective measurement; 3) test of hedonic by the panelists subjectively; 4) test the correlation between hedonic test with several quality variables are measured objectively; and 5) determination of the critical point as the critical limit. The results showed that the quality parameters those can be used as a critical quality parameter are the color (L value on the chromameter) and weight lost to the critical value for each L value is 78.51 for and weight lost is 10%. The use of critical quality parameters in determining the shelf-life of fresh-cut cauliflwers can be done by selecting one of the faster parameter reaches a critical point or can use both of them.